Sorption of Cr(VI), Cu(II) and Pb(II) by growing and non-growing cells of a bacterial consortium - Sannasi, P.; Kader, J.; Ismail, B.S.; Salmijah, S. (Elsevier, 2006)
This paper reports the sorption of three metallic ions, namely Cr(VI), Cu(II) and Pb(II) in aqueous solution by a consortium culture (CC) comprising an acclimatised mixed bacterial culture collected from point and non-point sources. Metal sorption capability of growing and non-growing cells at initial pH of between 3 and 8 in the 1–100 mg/L concentration range were studied based on Qmax and Kf values of the Langmuir and linearised Freundlich isotherm models, respectively. Maximal metal loading was generally observed to be dependent on the initial pH. Growing cells displayed significant maximal loading (Qmax) for Pb(II) (238.09 mg/g) and Cu(II) (178.87 mg/g) at pH 6 and at pH 7 for Cr(VI) (90.91 mg/g) compared to non-growing cells (p < 0.05). At the pH range of 6–8, growing cells showed higher loading capacity compared to non-growing cells i.e. 38–52% for Cr, 17–28% for Cu and 3–17% for Pb. At lower metal concentrations and at more acidic pH (3–4) however, non-growing cells had higher metal loading capacity than growing cells. The metal sorption capacity for both populations were as follows: Pb(II) > Cu(II) > Cr(VI).